G protein activation subunit genes in ovarian hemangioma. A systematic review - Baluswamy, Dr .Gayathri; Shunmugavelu, Dr. Karthik (Student's Journal of Health Research Africa, 2025)
Background Heterotrimeric G-proteins transmit signals from G-protein-coupled receptors (GPCRs) to the cell interior, modulating physiological activities based on specific tissue targets. While the fundamental schemes of G-protein regulation and signaling are well-documented, their specific role in rare neoplasms like ovarian hemangiomas remains an emerging area of study. Ovarian hemangiomas are uncommon; most are characterized by isolated reports of peculiar clinical manifestations or morphologic features. To fully characterize the clinicopathologic correlations of ovarian hemangiomas and assess the importance of hormone receptors in their pathogenesis, researchers are increasingly investigating the G protein-activating subunit gene, particularly mutations in GNAQ. In other vascular tumors, somatic mutations in these G-protein subunits trigger constitutive activation of downstream pathways, such as MAPK/ERK, driving endothelial proliferation. Understanding these molecular drivers is essential for distinguishing these benign vascular lesions from malignant ovarian cancers and for developing targeted diagnostic markers that bridge the gap between heterotrimeric G-protein signaling and rare gynecological pathology. Material and Methods Major databases such as Medline were explored through a detailed literature search, resulting in a systematic review pertaining to G protein activation subunit genes in ovarian hemangioma. Results Eight original research scientific articles, dated between 2020 and 2024, about the mentioned topic were highlighted. Conclusions Ovarian hemangiomas are extremely uncommon tumors that can occur at any age and are discovered by accident after surgery or autopsy. The purpose of this article is to highlight that these neoplasms should be considered in the differential diagnosis of a hemorrhagic ovarian lesion, even though they are extremely uncommon in the ovary. Receptor-G protein interactions have been the subject of extensive research for over 40 years, yielding significant insights into one of the most fundamental systems in human physiology.